Public Ethics in Civil Service Police Unit (Satpol PP) of Makassar - Thaha, Rasyid (UI Scholars Hub, 2017)
This study aims to analyze public ethics in local government institutions. It is used as an attempt to create an institutional order that allows better ethics in the governance system involving governmental institutions and the public. The study was conducted on Satpol PP (Satpol PP) in Makassar by using qualitative method. This study outlines the fundamental problems in terms of personal and institutional affairs of the Satpol PP in Makassar. The result indicates that the main problem is not merely in Satpol PP itself, but also institutionally public ethics has not been imposed well. Theoretical reflection resulted from the study is that in the context of civil service police unit of Makassar, institutional ethics should be made possible to control personal ethics. Therefore, the direction of future policy should emphasize more on how to build the institutional ethics for the Satpol PP of Makassar.